Wakaf Tunai: Strategi dan Tantangan di Ranah Minangkabau - Gustina, Gustina; Lukman, Syukri; Sakti, Muhammad Rizki Prima; Alfarisi, Mohammad Fany (Jurnal Ilmiah Ekonomi Islam, 2024)
The endowment of money or cash waqaf has the potential to significantly improve the welfare of the community in the Minangkabau region, both socially and economically. This includes areas such as education, health, and poverty alleviation. However, there are several challenges that need to be addressed to achieve maximum effectiveness. The aim of this research is to assess the feasibility of cash waqaf and the challenges it poses through qualitative research. Data collection is conducted through structured interviews with various informants, including BWI (Badan Wakaf Indonesia), nadzir (endowment managers/institutions), wakif (endowment donors), and religious leaders. The expected outcome of this research is to identify strategies and solutions to overcome the challenges faced in developing cash waqaf programs in the Minangkabau region, in accordance with the traditional philosophy of "Adat Basandi, Syarak, Syarak Basandi Kitabullah" (Customary law based on Islamic law, and Islamic law based on the Qur'an).